Partisipasi Perempuan dalam Perencanaan Pembangunan Desa - Pratitis Offi Agnes; Diana Dewi Sartika; yunin - Yunindyawati (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
The aims of this research is to analyze the women’s participation in village development, and to determine the motivations of this in Pulai Gading area, Bayung Lencir, Musi Banyuasin region. The methodology used is descriptive qualitative research method and case study research used for the design. The primary and secondary data were used in this research. Selecting the informant using the purposive method. Analysis unit used is on individual level. This theory used social action from Talcott Parsons. Deep interviewing on the subjected parties; women and men, religious leader, officials, and documentation study used in collecting the data. Triangulation source used for the data validity check. Data analysis tehnique used are data reduction, data presentation, and conclusion. Low participation rate comes out as the result of this research as shown from participation types; mind, energy, mind and energy, and expertise. Two kinds of motivations; internal and external. The internal includes the willingness and ability in participating. Meanwhile the external includes surrounding’s opinion and government policy. The low education and economy background are the main internal inhibitions, in the other hand, the poor access of information, socio-culture factor, and geographical factor.